1290 CAN P1NP LEVELS INFLUENCE MANAGEMENT PLANNING FOR PATIENTS WITH A FRAGILITY HIP FRACTURE RECEIVING ANTI-RESORPTIVE MEDICATIONS?. (16th January 2023) - Kraidi, M; Wilkinson, I; Bandyopadhay, S; Griffiths, S
Abstract: Introduction: Procollagen-N-terminal-peptide (P1NP) is a bone formation marker. Bisphosphonates lead to a reduction in P1NP levels and levels are significantly elevated shortly after fracture. In older patients taking bisphosphonates who have had a further osteoporotic fracture there is a lack of evidence to guide ongoing osteoporotic management. Objectives: To assess if measuring P1NP in patients receiving Bisphosphonates treatment who develop neck of femur fractures helps guide further management in regards to long term bone protection treatment. Method: Retrospective descriptive cohort study of P1NP levels for the patients who presented with NOF# (>60yrs) and who were taking anti-resorptive medications. Cases were discussed in our complex bone health MDM and patient specific plans made accordingly. Results: 60 patients were identified between March 2017 and Sept 2021 had P1NP tested (2.6 % of the 2, 303 total fractures in this time). Mean age 83 years (F:M – 54:6 / # type - IC:EC – 34:26). Overall: 17 (28%) patients had significantly elevated PINP with identifiable reasons. 39 (65%) patients had supressed P1NP levels (< 35mcg/L) and 5(7 %) between 36-39 mcg/L. Of those with supressed P1NP: Patients taking treatment >5 years (n=9) – Treatment stopped for 6 patients, 2 changed treatment following DXA and 1 continued. On treatment 3-5 years (n=8) – 5 continued with treatment, 1 had further ix and 2 treatments changed On treatment 1-3 years (n=17) – 14 continued treatment, 2 treatments stopped, 1 treatment changed On treatment <1 year (n=16) – all continued the same treatment Conclusion: The measurement of P1NP has been helpful in making patient centred decisions in this cohort. It has added to the detailed discussions in the hip fracture bone health MDM and for 23% of patients with supressed bone turnover contributed to a change in management. Most changes occurred in those patients taking treatment for more than 5 years where the evidence of bone turnover suppression gives confidence to stop or change treatment.